"I can't drink alcohol if i'm alone": On thinking about gender violence and drug dependences (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2021)
Gender violence is related in a complex way to the world of drug addiction. We know that drug consumption spaces have been described in general as spaces of violence against women. However, gender violence has gone unnoticed in different areas of the world of drug addiction, from its impact on the use or abuse of drugs by women to the problems it generates for women victims when they decide to start a drug abuse program. recovery if they have addiction problems. My objective in this text is to present stories about gender violence in the world of drug addiction, pointing out debates and needs for thought and research.
Keywords: gender violence; drug addiction; recreational spaces; alcohol